O efeito da esplenectomia na resposta imune às infecções causadas pela Leishmania major e pelo Trypanosoma cruzi - Tatiani Uceli Maioli (2008)
The spleen is a secondary lymphoid organ, associated with blood circulation. This organ harbors different kinds of cells, like T and B lymphocytes, macrophages and dendritic cells, for this reason is very important in cytokines and antibodies production and immune response development. Splenectomy is a common practice, and in C57BL/6 mice we observed reduction of IFN-gamma concentration in the blood plasma. So, one of the aims of this work was to check the importance of spleen in the immune response against L. major. Is already known that, C57BL/6 mice are resistant and BALB/c mice are susceptible against this infection, and the resistance is IFN-gamma dependent. Although, splenectomy did not change the course of infection caused by L. major. We did not observe differences in resistance, nether in susceptibility. The lesion size, parasite load, tissue inflammation, IL-4, IFN-gamma and IL-10 production by lymph node cells and antibody secretion were not different between mice with or without spleen. So, splenectomy was not able to change the immune response development during L. major infection.Still studying the role of spleen in infectious disease, the second aim, was to investigate the consequences of splenectomy during T. cruzi infection. For this propose we used the model of infection of C57BL/6 mice with Y strain of T. cruzi. Our data showed that absence of spleen changed the dynamics of disease. We observed that mice without spleen had different parasitemia and more mortality index. These results were followed by reduction in IFN-gamma and TNF-alfa in blood and increase in IL-4 levels, nine days after infection. Together with these results, we observed reduction of all cytokines availed in liver and more parasites and inflammatory infiltrate in this organ, compared with control group. Mice without spleen also showed more parasites in the heart nine days after infection. There was also reduction in the immunoglobulin synthesis and strong reduction in red blood cells and hemoglobin concentration in splenectomized mice compared with control mice. We also observed reduction in the number of bone marrow cells. This data was correlated with alteration in reticulocytes number in blood, what shows decrease in bone marrow activity.Those results, suggest that splenectomy does not cause strong changes in immune response developed against infections, where the proliferation and first responses against the parasite happen in the inoculums site. But, seems to increase the susceptibility to protozoa disease, induced by different way and have quickly parasite dissemination, like infection caused by T. cruzi.